Quality test entrance examination for full-time second-level in Midwifery faculty – 5-year retrospective analysis - Panczyk, Mariusz; Belowska, Jarosława; Rebandel, Henryk; Gotlib, Joanna (Nursing in the 21st Century, 2016)
QUALITY TEST ENTRANCE EXAMINATION FOR FULL-TIME SECOND-LEVEL IN MIDWIFERY FACULTY – 5-YEAR RETROSPECTIVE ANALYSIS Aim. Quality assessment of the test entrance examination used for selection of candidates for full-time second-level studies in Midwifery at the Medical University of Warsaw. Material and methods. Five grade-years of candidates (N = 335, 100% of women) who took the entrance exam for Midwifery between 2009/10 and 2013/14. Data collected was related to results of the test examination for studies (total score and scores divided into thematic blocks). Parameters of descriptive statistics were set. Ease and differentiating power of questions and reliability of tests were assessed (alpha-Cronbach). Discriminatory indexes for thematic blocks of the test were set. Calculations were performed in STATISTICA 12.5. Results. The most optimal selection of questions in terms of ease and differentiating power was recorded for the 2009/10 test. None of the editions of the exam met the minimum requirements for the internal consistency of measurement. The best results concerning the reliability of the measurement was observed for the 2009/10 test. Analysis of differentiating power of questions in thematic blocks indicates the diversity of this quality parameter. Very high differentiating index was recorded for the block of questions on specialist care in 2009/10 (0.535), and the lowest in 2013/14 exam (0.150). Conclusions. 1. It is necessary to improve the quality of exam questions in terms of difficulty and differentiating power. 2. Quality of subsequent editions of the admission examination should be monitored, in particular with regard to the control of the reliability of this qualifying tool.